Construction grammar across borders - Torrent, Tiago Timponi; Da Silva Matos, Ely Edison; Sathler Sigiliano, Natália (Benjamins current topics, 2022)
"Since its foundation in the 1980's, Construction Grammar has been crossing the traditionally imposed borders. From superimposed levels of analysis to the lexicon-grammar continuum, the constructionist approach to language has been built by, quoting Charles Fillmore, by "the insistence on seeing specific grammatical patterns as serving given semantic (and often pragmatic) purposes, and in the effort to construct a uniform theory capable of presenting both the simplest and most general aspects of language and the large world of complex grammatical structures". In this volume, five chapters derived from the plenary talks at the 9th International Conference on Construction Grammar provide a sample of the bridges the insistence and effort of construction grammarians have built in the past three decades with other analytical models - namely Cognitive Grammar and Collostructional Analysis -, perspectives - Diachronic Construction Grammar - and applications - Language Pedagogy and Natural Language Understanding. Originally published as special issue of Constructions and Frames 12:1 (2020)"--